Studi Tentang Profesionalisme Guru dalam Pembelajaran Daring Berdasarkan Akreditasi Sekolah di Sekolah Menengah Kejuruan - Mhd Safiq Adzkia; Mukhlidi Muskhir (Journal of Counseling, Education and Society, 2022)
The problem in this study is that the professionalism of teachers is currently still low, the majority of teachers are less able to adapt to the skills of 21st century teachers, lack of teacher motivation in improving self-quality due to not being able to compete and not ready to keep up with the times and the lack of teacher ability to apply 21st century skills. at SMK Negeri 2 Sungai Penuh. The purpose of this study is to find out how the professionalism of teachers in online learning is based on school accreditation at SMK Negeri 2 Sungai Penuh. The research method used is a mix method (quantitative and qualitative). The population in this study were 95 students of class X TITL. The sample in this study amounted to 95 people. The sampling technique used is total sampling. The data analysis technique used is descriptive and Respondent's Level of Achievement (TCR). The results showed that the professionalism of teachers on the digital age literacy indicator was 45.71% with a bad interpretation. In the inventive thinking indicator, a value of 46.92% was obtained with a bad interpretation. On the indicator of effective communication obtained a value of 46.92% with a bad interpretation. In the high productivity indicator, a value of 48.07% was obtained with a bad interpretation. Overall, the teacher's professionalism got a score of 46.90% with a bad interpretation. So it can be concluded that the professionalism of teachers in online learning based on school accreditation at SMKN 2 Sungai Full is in a bad interpretation.